An observation on street furniture in Kuala Lumpur City Centre (KLCC) park - Mat Rani, Ruzaimi; Hashim, Khairusy Syakirin Has-Yun (IIUM Press, 2009)
Seats and bins are two major components of street furniture that are always used by the public in any urban park. There are many issues the arise from these two components (seats and bins) such as cleanliness, safety, comfort, and maintenance. Each of these issues has its own criteria that need to be identified and understood to improve the environment of an urban park. The intention of the research was to identify types of design, material used, and potential and constrains face by these elements on the site. The Kuala Lumpur City Centre (KLCC) has been identified as the study for this research. This park can be considered as the most successful park in terms of the facilities and services provided to be public. Observation has been done during a few site visits (in year 2003) to KLCC park to identify the seats and bins design and conditions. Data collection and analysis were done by using photographs. From the observation, some interesting findings related to the design and conditions have been identified from the KLCC park area.